2002
DOI: 10.1097/00007632-200203150-00008
|View full text |Cite
|
Sign up to set email alerts
|

Curve Prevalence of a New Classification of Operative Adolescent Idiopathic Scoliosis

Abstract: A new comprehensive classification system for operative adolescent idiopathic scoliosis found all 606 consecutive cases of adolescent idiopathic scoliosis classifiable, with the Type 1, main thoracic curve pattern, the most common curve type found (51%). This new classification system appears to correlate with treatment of surgically structural regions of the spine fused in 90% of cases by the objective radiographic criteria used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
4
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(108 citation statements)
references
References 22 publications
5
92
4
7
Order By: Relevance
“…Yet many surgeons prefer to fuse both curves. One study showed that selective thoracic fusion was performed in 62% of patients with Lenke 1C curves [14]. This study found that both the thoracic and lumbar curves are fused in 38% of the Lenke 1C curves.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Yet many surgeons prefer to fuse both curves. One study showed that selective thoracic fusion was performed in 62% of patients with Lenke 1C curves [14]. This study found that both the thoracic and lumbar curves are fused in 38% of the Lenke 1C curves.…”
Section: Introductionmentioning
confidence: 86%
“…The King Type II curve is known as the ''false double major'' pattern, because the lumbar curve shows less magnitude and more flexibility on side-bending films which suggests that it is a compensatory curve present only to maintain coronal balance in the setting of a fixed thoracic curve. The King Type II curve was later reclassified by Lenke et al [13][14][15] as Lenke 1C, 2C, 3C, and 4C curves. Controversy exists over the treatment of the compensatory lumbar curve in King Type II curves [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Elias Lenke et al 15 , em estudo multicêntrico retrospectivo classificaram, de acordo com King 24 , 606 pacientes, e encontram 51% de curvas do tipo I, 20% do tipo II, 11% do tipo III, 3% do tipo IV, 12% do tipo V e 17,3% do tipo VI, já no nosso estudo encontramos a maioria das curvas torácicas tipo II de King seguido do tipo III.…”
Section: Discussionunclassified
“…Do ponto de vista acadêmico, o nosso trabalho tem o objetivo de levantar dados epidemiológicos sobre escoliose vertebral em nossos estado, assim como classificar as escolioses idiopáticas do adolescente (EIA) segundo Nery et al 13 , Lenke et al 14,15 , e Winter et al 16 . para escoliose congênita e neuromuscular ,respectivamente, para no futuro definir a melhor forma de tratamento.…”
Section: Introductionunclassified
“…The Lenke classification system for AIS was utilized, which has been shown to be accurate and reproducible and correlates with treatment of surgically structural regions of the spine [12,13,21]. Multiple radiographic measurements were assessed on the preoperative, immediate postoperative standing, and final postoperative long cassette biplanar radiographs.…”
Section: Methodsmentioning
confidence: 99%